Studi Evaluatif Model Khotbah Topikal Bagi Pengkhotbah Kristen - Yosua Sibarani (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2020)
Sermon plays an important role in Christian worship because it is the proclamation of God's word to the people. There are several models of preaching that can be applied by the preacher, one of which is the topical preaching model. Unfortunately, there are preachers who do not understand the essence of topical preaching by using Bible verses as a cover for other topics the preacher wants to address. This study is descriptive-evaluative about the topical preaching model and how it is implemented for Christian preachers so that readers are able to reconstruct the meaning of the topical sermons that have been carried out so far. This study finds that topical preaching is preaching that has advantages and disadvantages. This sermon model is in demand by many preachers because it is easier to prepare and effective in delivery. However, the preacher needs to be aware of the abuse of the topical method of inserting ideas into the biblical text (eisegesis). In fact, all preaching methods including topical must be exposition with the correct hermeneutic method.